ФОРМЫ СОСЛАГАТЕЛЬНОГО НАКЛОНЕНИЯ НЕМЕЦКОГО ЯЗЫКА (TAMADDUN NURI JURNALI, 2024)
The main goal of this article is to analyze the conjunctive mood in the German language and study its types. The conjunctive mood in the German language was studied as a grammatical category.